Modifying the multisensory perception of a carbonated beverage using auditory cues - Zampini, M; Spence, C (2005)
Our perception of the level of carbonation in a beverage often relies on the integration of a variety of multisensory cues from vision, oral-somatosensation, nociception, audition, and possibly even manual touch. In the present study, we specifically investigated the role of auditory cues in the perception of carbonation in beverages. In Experiment 1, participants rated a series of sparkling water samples in terms of their perceived carbonation using a visual analogue scale. The water sounds were modified by changing the loudness and/or frequency composition of the auditory feedback emitted by the water samples. The carbonated water samples were judged to be more carbonated when the overall sound level was increased and/or when the high frequency components (2-20 kHz) of the water sound were amplified. In Experiment 2, we investigated whether the perception of carbonation of physically different water samples (still, semi-sparkling, and sparkling) varied as a function of the distance at which the beverage was held from the participant. The sparkling water samples were evaluated as being more carbonated when they were held close to the ear rather than further away. In Experiment 3, we investigated whether the auditory manipulations reported in Experiment 1 might also influence the perception of the level of carbonation and oral irritation of water samples in the mouth. The results revealed that neither perceived carbonation nor the perceived oral irritation were influenced by variations in the level of auditory feedback. Taken together, these results highlight the significant role that auditory cues play in modulating our perception of the carbonation of beverages in the hand, and the dominance of oral-somatosensory and nociceptive cues over auditory cues in the perception of carbonation of beverages in the mouth. © 2005 Elsevier Ltd. All rights reserved.